Integrating Food Involvement and Destination Experiential Performance into the Gastronomic Place Attachment Framework - Isyanto, Puji; Yosepha, Sri Yanthy; Yani, Dini (Integrasi Sains Media, 2026)
Gastronomic tourism has evolved from a supplementary activity into a primary driver of destination satisfaction and tourist behavior. Grounded in the Stimulus-Organism-Response (S-O-R) framework, this research examines the mechanical transition from internal psychological traits to sustained destination loyalty. Specifically, the study investigates the structural relationships between Food Involvement (FI), Perceived Authenticity (PA), Gastronomic Sensory Appeal (GSA), Destination Experiential Performance (DEP), Gastronomic Place Attachment (GPA), and Revisit Intention (RI). Utilizing a quantitative, cross-sectional design, data were collected from 300 tourists in Bandung, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all seven hypothesized relationships are statistically supported. Food involvement serves as a potent internal stimulus that dictates the intensity of both cognitive authenticity and sensory appraisals. These organismic states collectively determine the experiential performance of the destination, which functions as the primary bridge to forming emotional place attachment and revisit intentions. Notably, the findings reveal that while sensory appeal provides physiological gratification, the cognitive validation of authenticity remains the dominant driver of experiential performance for highly involved tourists, functioning as an application of their gastronomic literacy. These insights provide a strategic framework for Destination Management Organizations (DMOs) to leverage culinary heritage as a tool for building destination brand equity and long-term tourist loyalty.